Student Affairs Committee Meeting Minutes, April 12, 2018 - Student Affairs Committee, Valdosta State University Faculty Senate (Valdosta State University Archives and Special Collections, 2018)
with Guest Speakers – Dr. Carr and Dr. Friedhoff (UA/19/1/ER3/003).
Keywords: Faculty Senate; Student Affairs Committee; Valdosta State University; Corporate minutes